THE IMPLEMENTATION OF BAKER’S CULTURAL SUBSTITUTION STRATEGY IN ENGLISH-INDONESIAN SUBTITLING OF FROZEN II - Malikatus Saidah; Januarius Mujianto (JELLT (Journal of English Language and Literature Teaching), 2021)
This study provides an analysis of cultural substitution strategy used in movie script. The objective of this study is to describe how the implementation and how the achievement of this strategy in movie script. The data were taken from of English and Indonesian subtitles FROZEN II (2019) movie. The descriptive qualitative approach applied in this study. The results of this study were no cultural substitution strategy were found in FROZEN II movie script, however there were 5 types of translation strategy proposed by Mona Baker found in English and Indonesian subtitles of FROZEN II movie. They are translation by using a more general word with 770 data (70%), translation by using paraphrase using unrelated word with 157 data (14%), translation by using paraphrase using loan word or loan plus explanation word with 60 data (5%), translation by using related words with 59 (5%), and translation by using more neutral/less expressive with 22 data (2%). Based on the findings, the researcher found that translation by using more general word becomes the strategy that the most frequent in movie script with 770 data (70%).For the achievment of equivalence the data shown that is appropriate because the score of the appropriateness is 700-100.